Frequency-based leak signature investigation using acoustic sensors in urban water distribution networks. (January 2023) - Sitaropoulos, Konstantinos; Salamone, Salvatore; Sela, Lina
Abstract: Cities worldwide have been plagued by water pipe leaks for many decades, resulting in financial losses, public health risks, and environmental impacts. Current practice still relies heavily on periodic and localized inspection rather than long-term continuous monitoring, and since water pipelines are buried underground, leaks can often go undetected for prolonged periods. Noninvasive acoustic-based methods for continuous pipeline monitoring have gained increasing popularity the past decade thanks to the recent advances in sensing and communication technology. Previous research indicates that hydrophones, in particular, are capable of effectively detecting leak-induced acoustic waves inside a water pipe. However, most studies to date have been limited to either controlled or field test-bed settings; hence, findings might not generalize well to real-world complex pipe networks. Through rigorous leak tests conducted in a real water distribution network and an extensive analysis of the field-collected acoustic signals, the current study aims to test the applicability of low-cost, non-intrusive hydrophones attached to fire hydrants for continuous pipe monitoring and leak detection. Continuous wavelet transform, power spectrum, and band power analyses were employed to identify the leak signature and distinguish normal from leak acoustic data in various leak scenarios. Results indicate that the acoustic signals generated by the simulated leaks in this field study are characterized by a consistent increase in the power of the frequency band 150–450 Hz primarily, whereas background noise levels and conditions significantly vary depending on the location of the sensor in the network. Realistic conditions in urban water distribution networks, including background noise, complicated topology, and varying pipe size and material, are still posing significant challenges for cost-effective and widespread implementation of acoustic-based sensors to achieve continuous monitoring in water pipe networks for leak detection. Even though further research and development is required to handle the highly variable conditions of real systems, the low-cost hydrophones tested in this work demonstrated potential in detecting low-flow leaks in simple and complex pipe topologies.